Influence of exercise contraction mode and protein supplementation on human skeletal muscle satellite cell content and muscle fiber growth - Farup, Jean (J Appl Physiol (1985), 2014)
Skeletal muscle satellite cells (SCs) are involved in remodeling and hypertrophy processes of skeletal muscle. However, little knowledge exists on extrinsic factors that influence the content of SCs in skeletal muscle. In a comparative human study, we investigated the muscle fiber type-specific association between emergence of satellite cells (SCs), muscle growth, and remodeling in response to 12 wk unilateral resistance training performed as eccentric (Ecc) or concentric (Conc) resistance training ± whey protein (Whey, 19.5 g protein + 19.5 g glucose) or placebo (Placebo, 39 g glucose) supplementation. Muscle biopsies (vastus lateralis) were analyzed for fiber type-specific SCs, myonuclei, and fiber cross-sectional area (CSA). Following training, SCs increased with Conc in both type I and type II fibers (P < 0.01) and exhibited a group difference from Ecc (P < 0.05), which did not increase. Myonuclei content in type I fibers increased in all groups (P < 0.01), while a specific accretion of myonuclei in type II fibers was observed in the Whey-Conc (P < 0.01) and Placebo-Ecc (P < 0.01) groups. Similarly, whereas type I fiber CSA increased independently of intervention (P < 0.001), type II fiber CSA increased exclusively with Whey-Conc (P < 0.01) and type II fiber hypertrophy correlated with whole muscle hypertrophy exclusively following Conc training (P < 0.01). In conclusion, isolated concentric knee extensor resistance training appears to constitute a stronger driver of SC content than eccentric resistance training while type II fiber hypertrophy was accentuated when combining concentric resistance training with whey protein supplementation.